Efektivitas Terapi Relaksasi Nafas Dalam Terhadap Penurunan Tingkat Kecemasan Pasien Praoperasi Di Rumah Sakit Umum Daerah - Ayu Sholehah (CV. SINAR HOWUHOWU, 2025)
Preoperative anxiety is a common psychological issue experienced by patients before undergoing surgery, which may affect physiological stability and surgical outcomes. This study aimed to analyze the effectiveness of deep breathing relaxation therapy in reducing preoperative anxiety levels among patients in a Regional General Hospital. This research employed a quasi-experimental design with a pretest-posttest control group design. A total of 40 participants were divided into two groups: the intervention group, which received deep breathing relaxation therapy, and the control group, which did not receive the intervention. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI) before and after the intervention. The results showed a significant reduction in anxiety levels in the intervention group (p = 0.000, p < 0.05), while no significant change was observed in the control group. The deep breathing relaxation therapy was proven effective in decreasing anxiety through the regulation of the parasympathetic nervous system, which induces calmness and reduces muscle tension. It can be concluded that this therapy serves as a simple, safe, and efficient non-pharmacological intervention to reduce preoperative anxiety and enhance evidence-based nursing care quality in hospital settings.